Gerd E. G. Westermann (11.05.1927–5.11.2014) - Riccardi, Alberto Carlos (2015)
Gerd Ernst Gerold Westermann was born on May 11, 1927 in Berlin. In 1930, his family moved to the medieval town of Goslar, the center of the “Klassische Geologische Quadratmeile”, described by J.W. Goethe. When the loss of Germany's eastern territories in 1945 destroyed Gerd’s childhood dreams to become a forester, he followed his other interests – geology and fossils. After a brief service in the Volksturm and a few months internment in what he described as “a starvation camp under free skies”, he finished high school in 1946. German universities having essentially closed down, he spent part of the following two years working underground in the famous medieval gold and silver (lead-zinc) mines, Rammelsberg and Bad Grund of the Harz Mountains, around Goslar, and studied ore paragenesis in the mine laboratories; made many excursions into the surrounding “Squaremile” (c. 7 × 7 km); guided students of the near-by Mining Academy of Clausthal, studied geology books; made up collections of hand-shaped rock specimens of rectangular shapes for teaching; and catalogued 4,000 specimens of fossil invertebrates in the Goslar Museum. To win a place at a university, he then worked producing bricks for the rebuilding of the universities destroyed during the war. Making the best of it, he invented a method to cast and collect large Hauterivian ammonites exposed by the power shoval directly in clay pit, which ended up at the Hannover Geological Survey.